Freeze-thaw stability of beef hamburger patties with carrageenan - Chua, Penny Siy
ABSTRACT A freeze-thaw stability of beef hamburger patties with carrageenan was conducted. Phase I dealt with the production and storage o fbeef hamburger patties with varying kind of carrageenan. The beef patty samples were subjected to three freeze-thaw cycles. Phase II dealt with the evaluation of freeze-thawed beef hamburger patties through physico-chemical tests and sensory evaluation. In the physico-chemical tests, results showed that in between treatments, the iota and iota-kappa treated beef patty samples had higher pH, water holding capacity, and thaw drip than the control. These treatment also had lower cooking looses than the control. As between cycles, results showed that the values of the respective properties decreased as the number of freeze-thaw increased. In the sensory a, results showed that iota and iota-kappa treated beef patty samples generally exhibited better brown color, texture, juiciness, chewiness, compactness, springiness, and overall acceptability than that of the control in all the freeze-thaw cycles. Aroma and beef flavor were not distinct among the three treatments regardless of the freeze-thaw. Statistical analysis using Analysis of Variance at a 0.05 level of significance showed significant differences in the water holding capacity and cooking loss between cycles. here were also significant differences in the color and springiness of the beef patty samples between treatments and between cycles.